Efficacy of opioid-free anesthesia in short-term recovery following laparoscopic-assisted colorectal tumor resection: a randomized trial - Zhang, Liang; Yu, Xian-Hua; Zhang, Hui-Ming; Wang, Sheng; Chen, Jian-Long; Li, Xue-Shan; Chen, Zhi-Yuan (Frontiers in Oncology, 2025)
ObjectiveThis study aims to evaluate whether opioid-free anesthesia is non-inferior to opioid-based anesthesia in terms of short-term recovery quality in patients undergoing laparoscopic-assisted colorectal tumor resection.MethodsA randomized controlled trial was conducted with 102 participants, who were randomly assigned to one of two groups: opioid-free general anesthesia with thoracic epidural anesthesia (OFA) group and opioid-based general anesthesia with compound transversalis fascia nerve block (OA) group. The primary observation outcomes were the preoperative and postoperative Quality of Recovery-40 (QoR-40) questionnaire scores.ResultsNo statistically significant differences were observed in preoperative or postoperative QoR-40 scores between the two groups (p = 0.05). However, the OFA group demonstrated a significantly longer recovery time in the recovery room compared to the OA group (p< 0.05). No significant differences were observed between the two groups in postoperative nausea and vomiting, time to first meal after surgery, postoperative drainage tube removal time, postoperative sufentanil dose, or postoperative 24-hour numerical rating scale (p > 0.05).ConclusionOpioid-free general anesthesia is not superior to opioid-based general anesthesia with transversalis fascia nerve block in terms of short-term postoperative recovery quality following laparoscopic-assisted colorectal tumor resection.Clinical Trial Registrationhttps://www.chictr.org.cn/, identifier 2023-12-08.